Odpowiedzi

  • Użytkownik Zadane
2009-11-15T12:06:23+01:00
7(x²-3x-2)-3(x²-6x+1)=7x²-21x-14-3²+18x-1=7×0,2²-21×0,2-14-9+18×0,2-1=7×0,04-21×0,2-14-9+18×0,2=0,28-4,2-14-9+3,6=-23,32

x(3xy-y)-y(x²-xy+x)=3x²y-xy-x²y+xy²-xy

nie wiem co w 2 oznacza y więc rozwiązałam do połowy ;)
2009-11-15T12:06:55+01:00
A ) 7(x²-3x-2)-3(x²-6x+1) dla x = - 0,2

7(x²-3x-2)-3(x²-6x+1)=7x²-21x-14-3x²+18x-3=4x²-3x-17
4x²-3x-17= 4*(- 0,2)²-3*(- 0,2)-17=4*0,04+0,6-17=0,16+0,6-17=-16,24

b)x(3xy-y)-y(x²-xy+x) dla x = - 1 , y =⅕
x(3xy-y)-y(x²-xy+x)=3x²y-xy-yx²+y²x-yx=2x²y+y²x-2xy

2x²y+y²x-2xy=2*(-1)²*⅕+(⅕)²*(-1)-2*(⅕)*(-1)=⅖-1/25+⅖=-1/25
4 3 4
2009-11-15T12:45:06+01:00
7(x²-3x-2)-3(x²-6x+1) dla x = - 0,2

7 ( [-0,2 ]² - 3 * [-0,2] -2) - 3 * ( [-0,2]² - 6*[-0,2] + 1 ) =
7* ( 0,04 + 0,6 -2 ) - 3*( 0,04 + 1,2 +1) = 7 * ( -1,36) - 3* (2,24) =
-9,52 - 6,72 = -16,24

x(3xy-y)-y(x²-xy+x) dla x = - 1 , y =⅕

-1 ( 3 * (-1) - ⅕) - ⅕ ([-1²] - {[-1] * ⅕ } + [-1] ) =
-1 ( -3 - ⅕) - ⅕ ( 1 - ⅕ + 1 ) = -1 * (-3⅕) - ⅕ ( 1⅘)=
3⅕ - ⁹/₂₅ = ¹⁶/₅ - ⁹/₂₅ = ⁸⁰/₂₅ - ⁹/₂₅ = ⁷¹/₂₅ =
coś poplątałam w drugim ;/ .;p